Transfert and Reception of Speeches and Practices in the Atlantic Space: the Example of Chilean Urban Sanitary Engineering (1981-1905) - Fernandéz, Enrique (Revista de Historia Social y de las Mentalidades, 2018)
The article proposes an analysis of the process of circulation, reception and application of speeches and practices of urban Sanitary Engineering in the Atlantic space. We analyze the interaction between an international movement -the development of sanitary engineering- and Chilean reception conditions from the beginning of the professionalization of Chilean engineers to the inauguration of the sewer works of Santiago de Chile.